(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
The spiritual upbringing of preschool children begins with the family. The child is parents who put the foundations of morality and spirituality. Helping to achieve these goals: Support for the illicacy of the baby: Pictures that the child respects him only if parents respected by their personality; Introducing the child with culture: art works have a beneficial effect on its thinking and actions; Communication with the child is a state of information on preschool education, family and society in child rearing.